Molecular Dynamics Simulation of Ice Indentation by Model Atomic Force Microscopy Tips - Gelman Constantin, Julián (2015)
We have performed extensive MD simulations of nanoindentation of an ice slab with model AFM tips. We found the presence of a quasi liquid layer between the tip and the ice for all explored indentation depths. For the smallest tip studied (R = 0.55 nm), force versus indentation depth curves present peaks, related with the melting of distinct monolayers of ice, and we were able to calculate the work (free energy) associated with it. For a larger tip (R = 1.80 nm), size is no longer commensurate with average monolayer thickness and we did not nd a clear structure in force curves. This work can help guide the interpretation of experimental AFM indentation of ice and other crystalline solids. More specifically, it provides guidelines for tip sizes where layer-by-layer melting can be achieved and for the order of magnitude of forces that need to be detected.